Uso da Análise Multicritério para Identificação das Zonas Compatíveis a Implantação de Aterro Sanitário em Consórcio Intermunicipal - Souza, Kassio Henrique Gama (2023)
Growing population combined with changes in consumption patterns are the main activities that have been contributing to the increase in generation of Urban Solid Waste, a problem that vast majority of Brazilian cities are not prepared for the environmentally appropriate final disposal of this waste, garbage is disposed of in open-air and in the presence of people and animals. This situation contributed to the creation of the Intermunicipal Consortium Sustainable Development Integrated Region of– RIDES, a region composed of 10 municipalities, which nine had their waste in dumps and controlled sanitary landfills and nowadaysoutsource the final disposal. This research sought to select suitable areas for the implementation of joint sanitary landfill to assist in management of solid waste in these municipalities. For this, thematic maps were produced based on environmental legislation and technical standards and using Boolean Logic. The thematic map generated from analysis was divided into two classes of level and aptitude for sanitary landfill implementation being Apt and Not Apt. As a result, areas suitable for project installation were obtained. The results indicate that the proposed objective was achieved and this method integrated with the GIS provides a procedure for locating areas for sanitary landfills installation.